Assessment of Physicochemical and Biochemical Qualities of Tannery Effluents of Hazaribagh, Dhaka, and Comparison with Non-Tannery Water Samples - Islam, Laila N.; Rahman, Adua; Mahmud, Zimam; Nabi, A. H. M. Nurun; Hossain, Mahmud; Mohasin, M. (International Journal of Environment, 2015)
NOTE: on 21st May 2015, the authors Mahmud Hossain and M Mohasin were added to the online information about the article. The PDF remains correct. In this study the physicochemical and biochemical qualities of the tannery effluents were analyzed to determine the pollution load of the openly released wastewaters in the environment and the findings were compared with the non-tannery waters. Fourteen samples of factory effluents were collected from the leather tanning industrial zone of Hazaribagh, Dhaka, and 13 non-tannery water samples were collected from different parts of Dhaka city. The effluents were mostly colored; their pH varied from highly acidic to basic values while densities were not much different from the non-tannery waters. The chromium contents of the effluents varied from less than 0.002 to 18.97 mg/L and the chemical oxygen demands (COD) varied from 90 to 6500 mg/L, which were significantly higher than those of non-tannery waters. There was a strong direct correlation between chromium content and COD (p<0.01) indicating that chromium was hugely responsible for pollution caused by tannery effluents. The tannery wastewaters were highly toxic to brine shrimp nauplii (lethality: about 82%), and chromium was responsible for biotoxicity of the effluents since a direct significant correlation (p<0.021) was found between chromium content and lethality. Storage of the wastewater samples for 2 to 8 months at room temperature showed rise in the pH values possibly due to microbial action that resulted in decrease of dissolved chromium content from a mean value of 7.94 to 5.09 mg/L. These findings demonstrated that the presence of high concentrations of chromium and other chemicals in the untreated tannery effluents were contributing adverse effects on the environment and ecosystem. DOI: http://dx.doi.org/10.3126/ije.v4i1.12179 International Journal of Environment Volume-4, Issue-1, Dec-Feb 2014/15, page: 68-81